2020
DOI: 10.1002/hyp.13743
|View full text |Cite
|
Sign up to set email alerts
|

Determining Hydrologic Pathways of Streamflow Using Geochemical Tracers in a Claypan Watershed

Abstract: Despite the low permeability of claypan soils, groundwater has been heavily contaminated by nitrate in agricultural watersheds dominated by claypan soils. However, it is unclear how nitrate concentrations in groundwater affect stream water quality. In this study, streamflow pathways were investigated using natural geochemical tracers in the 73-km 2 Goodwater Creek Experimental Watershed in northeastern Missouri. Samples were collected from 2011 to 2017 from stream water (weekly-biweekly), precipitation (eventb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Insights from previous field investigations help to explain why low soil permeability leads to the dominance of SOF or SSF1. Previous field investigations demonstrated that the reported low saturated hydraulic conductivities in some regions (e.g., Till Plains and the Dissected Till Plains) might be attributed to the existence of a relatively impermeable soil layer (Liu et al., 2020; Zimmer & Gannon, 2018), for example, claypan which is a naturally formed argillic horizon (Bt). These impeding layers dampen deep percolation and favor the formation of a shallow and relatively permanent water table and generation of SOF or SSF1.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Insights from previous field investigations help to explain why low soil permeability leads to the dominance of SOF or SSF1. Previous field investigations demonstrated that the reported low saturated hydraulic conductivities in some regions (e.g., Till Plains and the Dissected Till Plains) might be attributed to the existence of a relatively impermeable soil layer (Liu et al., 2020; Zimmer & Gannon, 2018), for example, claypan which is a naturally formed argillic horizon (Bt). These impeding layers dampen deep percolation and favor the formation of a shallow and relatively permanent water table and generation of SOF or SSF1.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Calcium, Mg 2+ , and Na + were considered to be conservative, while K + was quasi-conservative. The relative rootmean square errors (RRMSE) were lower in 1-D and 2-D mixing spaces for Ca 2+ , Mg 2+ , and Na + than for other ions, but the value of SO 4 2À was not unusually high compared to other studies (e.g., Liu et al, 2013;Liu et al, 2020), suggesting that SO 4 2À could be considered to be quasi-conservative as well.…”
Section: àmentioning
confidence: 62%
“…Second, it is easier to code the procedure from an operational perspective. Third, a low R 2 may still be significant at α = 0.001 with a large number of samples, as encountered in Liu et al (2020). A change was also made to validate EMMA results by simulating streamflow chemistry for conservative solutes.…”
Section: Diagnostic Tools Of Mixing Models and Endmember Mixing Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Endmember contributions were resolved following Liu et al (2017) and Liu et al (2020). To estimate statistical uncertainties associated with spatiotemporal variation of tracer concentrations in endmembers and analytical errors, standard deviation was used if multiple samples were available and the analytical errors of 1% for ionic composition and 0.2‰ for δ 18 O were used for a single sample.…”
Section: Endmember Contributions and Statistical Uncertaintiesmentioning
confidence: 99%